2021
DOI: 10.51747/publicio.v3i2.774
|View full text |Cite
|
Sign up to set email alerts
|

George Edward Iii Model

Abstract: Indonesia is a country with highest number of smokers in the world with high mortality. The dangers of smoking not only threaten active smokers but also passive smokers. Policies are necessary to protect and reduce its adverse effects of smoking. At the regional level in 2018, the Malang City Government passed a Regional Regulation that regulates Non-Smoking Areas (KTR). The realization and efforts to implement this regional regulation are the objectives of the research. Qualitative method is used, the focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
1
10
0
6
Order By: Relevance
“…The results of this research strengthen the argument that the implementation of the Prima Posyandu Program in Surabaya City has had a significant impact in reducing stunting rates. These findings support the argument that standard policies regulated by Presidential Regulations, Minister of Health Regulations, and Surabaya Mayor Regulations have become the basis for implementing this program (Ferguson & Clark, 1979;Setyawan et al, 2021). The aim of this program is to improve the quality of public health services, especially in efforts to reduce stunting rates, and the results reflect success in achieving this target.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of this research strengthen the argument that the implementation of the Prima Posyandu Program in Surabaya City has had a significant impact in reducing stunting rates. These findings support the argument that standard policies regulated by Presidential Regulations, Minister of Health Regulations, and Surabaya Mayor Regulations have become the basis for implementing this program (Ferguson & Clark, 1979;Setyawan et al, 2021). The aim of this program is to improve the quality of public health services, especially in efforts to reduce stunting rates, and the results reflect success in achieving this target.…”
Section: Discussionsupporting
confidence: 74%
“…An in-depth evaluation of the stunting reduction program implemented by the Surabaya City Government reveals the strategic success of innovative policies such as Prima Posyandu. These steps are based on a strong foundation of presidential regulations, minister of health, and mayoral regulations (Edwards & Sharkansky, 1979;Setyawan et al, 2021). Effective implementation of this policy not only resulted in a significant reduction in the number of children under five experiencing stunting, but also reflected efficient resource management by local governments (Bryson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to Edward III [13] the implementation of the policy will go well and according to the objectives also determined the disposition (attitude) where there must be a willingness to implement the policy and factors of the bureaucratic structure by implementing something that must be in accordance with the SOP and the distribution of responsibility. From the description of the research results, it can be concluded that the implementation of communication applications through online-based applications with schools that the kabos application has been implemented but is not optimal because there is a need for communication through outreach to users, in this case basic education supervisors, requires creativity and innovation in using supervisor applications.…”
Section: Application Application Communication Through An Online-base...mentioning
confidence: 99%
“…According to the model put forward by Edward III, there are four factors that influence the success or failure of implementing a policy, namely factors of resources, bureaucracy, communication, and disposition. [13].…”
mentioning
confidence: 99%
“…Jenis penelitian dalam penelitian ini adalah deskriptif dengan pendekatan kualitatif dengan menggunankan pendekatan teori dari George Edward III yang didasarkan pada 4 (empat) aspek yaitu komunikasi, sumber daya, disposisi, dan struktur birokrasi (Setyawan et al, 2021). Sumber data penelitian ini terdiri dari tiga yaitu sumber data primer yaitu berupa hasil wawancara dan observasi, sumber data sekunder yaitu data hasil olahan instansi yaitu dari Satuan Polisi Pamong Praja dan Kebakaran Kabupaten Trenggalek, dan yang terakhir adalah informan yang diambil dari pejabat fungsional Pol PP (Bungin Burhan, 2019;Sugiyono, 2017).…”
Section: Metode Penelitianunclassified